Професор Олександр Гаврилович Яхниця - видатний учений, талановитий педагог - Колесник, Юрій Михайлович; Волошин, Микола Анатолійович; Сирцов, Вадим Кирилович (Запорізький державний медичний університет, 2011)
Показана роль и значение организационной, научной деятельности профессора А.Г. Яхницы в создании кафедры анатомии человека Запорожского медицинского института и в формировании Запорожской школы морфологов. The role and importance of scientifi c and organizational work of professor A.G. Yakhnitsa in formation of Human anatomy department in Zaporozhye state medical university and in formation of Zaporozhye morphology school is given in the article.
Keywords: Олександр Гаврилович Яхниця; організаційна й наукова діяльність; Oleksandr Gavrilovic Yahnitsya; оrganizational and scientifi c activities